A Review on Tool Pin Geometry of Friction Stir Welding - Ahmed, Walaa H.; kadhum, Ali H.; Salleh, Mohd Shukor (Al-Khwarizmi Engineering Journal, 2024)
Friction stir welding (FSW) is an innovative solid joining operation that has recently been intensively adopted in welding various similar and dissimilar metallic materials, including aluminum, steel, titanium alloys, and others. The success of FSW relies on a set of parameters like rotational speed, travel speed, axial force, tool geometry, etc. The role of tool geometry (involving both pin and shoulder design) is highly important in producing sound and high-strength weld joints. Therefore, this research aims to review the latest published works regarding the performance of different tool geometries. The discussion of the findings of the cited works revealed that each tool pin design has shown different behavior due to the various stirring efficiencies of the materials being welded. All in all, the square threaded pin had the best geometry in terms of its mechanical properties compared to other pin designs. The threaded cylinders and threaded taper are most commonly utilized and offer good joints, while the maximum joint efficiency was achieved by the square pin profile and it reached 94% in some investigations.